Integral Education in the Context of the Process of Secularization - Szulist, Janusz; Babiński, Jarosław (Forum Teologiczne, 2022)
The purpose of this article is to demonstrate the threat that secularization poses with respect to the education process. The modern time is characterized by a secular shift in social relations and in the very concept of the human person. The paper points explicitly to the consequences of the materialization and technologization of life and proposes an integral education model as an alternative for the increasingly secularized society. Every human being is endowed with personal dignity and inalienable rights whose complete justification can only be uncovered within the context of revealed knowledge. Personality formation, which outlines the general purpose of education, includes not only corporeal and spiritual factors, but also factors of a religious nature that encourage transformation in the sense of achieving ever higher levels of perfection. It is argued that the integral education model can be applied in the areas of learning and work. The touchstone of any human development that takes into account religious factors is humanization, which is defined as making the world more humane in a constant relationship to God.